Economia libidinal bourdieusiana sob a luz negra do afropessimismo - Penna de Castro, Camila (2026)
This article explores the shifts that a metatheory would provoke in the libidinal «outline of a theory» of praxis that Bourdieu offers in his final writings. Metatheory is the term Frank Wilderson III and Jared Sexton use to present Afropessimism, and it shares with this later Bourdieu the effort to interpret social forms based on the libidinal energies invested. The article demonstrates that Afropessimism can interrogate, in an unusual way, the tacit and presumptive logic of Bourdieu’s libidinal economy, indicating to what extent certain human investments in social consecration are structurally articulated with Black suffering. The first part of the article presents the Afropessimistic approach and points to possible (mis)encounters with Bourdieu’s discussion of libido, distinction, and social consecration. The second part explores the tensions between the notions of symbolic violence and gratuitous anti-Black violence, starting from the discussion of consent and white ignorance. Throughout the discussion, we provide examples based on experiments in the academic environment using the theoretical approaches employed here. The conclusion attempts to map the underlying issues of social fields through the lens of Afropessimism.